2018
DOI: 10.1038/s41424-018-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Meconium microbiome associates with the development of neonatal jaundice

Abstract: ObjectiveNeonatal jaundice is a common disease that affects up to 60% of newborns. Gut microbiota mediated the excretion of bilirubin from the human body. However, the relationship between early gut microbiome and development of neonatal jaundice is not fully understood. Here we sought to characterize meconium microbiome of newborns and to clarify its association with risk of neonatal jaundice.MethodsWe conducted a nested case–control study with 301 newborns providing meconium samples from 2014 to 2015. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
2
25
2
Order By: Relevance
“…Our data also showed the beta diversity of meconium microbiome is significantly associated with delivery mode. It is contradictory to the previous reports (Dong et al, 2018;Hu et al, 2013) that the mode of delivery is unlikely a major contributor to shape this initial bacterial community as the meconium microbiota is mostly derived from the in utero environment. One possible reason for our result is the almost 100% overlapping between the delivery mode via C-section and antibiotic usage, in which the latter may affect the meconium microbiome composition significantly.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Our data also showed the beta diversity of meconium microbiome is significantly associated with delivery mode. It is contradictory to the previous reports (Dong et al, 2018;Hu et al, 2013) that the mode of delivery is unlikely a major contributor to shape this initial bacterial community as the meconium microbiota is mostly derived from the in utero environment. One possible reason for our result is the almost 100% overlapping between the delivery mode via C-section and antibiotic usage, in which the latter may affect the meconium microbiome composition significantly.…”
Section: Discussioncontrasting
confidence: 93%
“…Those studies contributed to a growing consensus that commensal bacteria are present in the intrauterine environment and may influence the bacterial colonization of babies before birth (DiGiulio et al, 2008;Jiménez et al, 2008;Rautava, Collado, Salminen, & Isolauri, 2012;Satokari, Grönroos, Laitinen, Salminen, & Isolauri, 2009) or during the delivery when the baby goes through the birth canal (Jašarević, Rodgers et al, 2015). Although this in utero colonization hypothesis has recently been questioned for its inconsistency, in part, due to the generally extreme low bacterial load in the intrauterine environment and to possible artifacts from environmental contaminations (Lauder et al, 2016;Perez-Muñoz, Arrieta, Ramer-Tait, & Walter, 2017), a growing number of studies have supported the existence of meconium microbiota and their association with health outcomes (Chu et al, 2016;Dong et al, 2018;Durack et al, 2018). It has been hypothesized that the central nervous system (CNS) and intestinal microbiota develop in parallel during the prenatal and early postnatal periods and interact during critical phases of development (Borre et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the major bacterium which formed infant gastrointestinal microbiota belonged to the Firmicutes and Proteobacteria phyla ( Nagpal et al, 2016 ; Dong et al, 2018 ; Nagpal and Yamashiro, 2018 ). Specifically, the colonization levels of several genera belonging to Firmicutes, such as Enterococcoceae , Lachnospiraceae , and Lactobacillus were significantly influenced by delivery mode ( Gronlund et al, 1999 ; Rutayisire et al, 2016 ).…”
Section: Discussionmentioning
confidence: 91%
“…Microbiota in meconium has been vastly studied due to its possible impact on infant's health and development and diseases that may be contracted during their early days as well as in the long term [ 2 , 9 , 10 ]. It was reported that the bacteria taxonomic diversity is relatively low at birth but increases over time as the infant is colonized with bacteria acquired from breast milk and the environment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%